PENGARUH KINERJA KEUANGAN DAN UMUR PERUSAHAAN TERHADAP MODAL INTELEKTUAL (Media Riset Akuntansi, 2022)
This study aims to determine the effect of financial performance, firm size and firm age on intellectual capital disclosure. The variables used to measure financial performance are leverage and profitability. The sample of this study consisted of 111 banking sector companies listed on the Indonesia Stock Exchange in 2015-2017. The method used in this research is multiple linear regression analysis. The results showed that leverage, profitability and firm size had no effect on intellectual capital disclosure. Meanwhile, the age of the company has a positive effect on the disclosure of intellectual capital.